Sustainable Clothing Buying Behavior of Generations X and Y (Marketing i Menedžment Innovacij, 2024)
This contribution addresses the sustainable clothing buying behaviour of Generations X and Y. The aim of the paper is to analyse the main features of sustainable clothing buying behaviour within Generations X and Y and to suggest some marketing activities for fashion companies. The theoretical background contains information from professional literature, scientific journals indexed in WOS and Scopus, and websites regarding the main trends in CSR, sustainable development, and sustainable buying behaviour, with a focus on the fashion industry. The analysis comprises multiple stages: the creation of a questionnaire through Google Forms, the selection of respondents from generations X and Y in the territory of the Slovak Republic, the analysis of respondents' answers through descriptive statistics, and the evaluation of research hypotheses via inductive statistics. Among the general research methods, historical-logical methods, analysis, synthesis, and comparison were used, whereas specialised research methods included methods of descriptive statistics and methods of inductive statistics implemented in the SPSS program. The questionnaire consisted of 11 questions based on previous research on the study topics and was completed by 139 respondents. The identification questions sought information from the participants about their identification as Generation X or Y, their gender, and their income. The next step was a comparison of shopping places, types of clothing, buying factors, and frequency and awareness of sustainable trends. The last 3 questions were framed according to previous research and were evaluated via descriptive statistics methods as well as inductive statistics. Research hypotheses are focused on relationships between the use of sustainable trends and belonging to a specific generation, the degree of influence of sustainable trends on buying behaviour and belonging to a specific generation, and the degree of rationality when purchasing clothes and belonging to a specific generation. On the basis of these tests, only the second hypothesis (influence of sustainable trends) was further analysed. Research results indicate that fashion brands can utilise slow fashion for different types of marketing communication to effectively target Generations X and Y, with a particular focus on influencer marketing on social networks. The limitations include various definitions of generations (birth years), possible cognitive distortions and the subjective answers of respondents. The fashion industry is an essential component of the creative industry and creative economy. Research could be extended by comparing sustainable clothing buying behaviour between inhabitants from the region with the above-average value of the regional NUTS3 creative index (Bratislava region) and inhabitants from other NUTS3 regions. Research could also be extended by comparing the effects of irrationality on generations in the context of behavioural economics. The end of the contribution expresses the benefits of this research for economics, the environment, and society.